Computer Programming for Selection of Boom Width and Tank Capacity of Field Sprayers (University of Khartoum Journal of Agricultural Sciences, 2023)
A computer programme was developed for selection ofboom width and tank capacity of field sprayer. The computer modelwas built up using Visual Basic (ver.6) computer programminglanguage in which input data were inserted directly and output resultswere obtained easily on the computer screen or as a printout. Themodel was verified with data collected from some agricultural privatecompanies in Gedarif area, Kenana agricultural implements factoryand some data from the literature. The validity of the model was tested,and the results showed close agreement between the fieldmeasurements and the computer model predictions. The sensitivityanalysis of the model revealed that changes in any of the inputparameters used could directly affect the output of the model, such asboom width, tank capacity and work rate. The accuracy of the modelwas also tested statistically. The model is helpful in proper sprayersmanagement and quick decision-making.